Efficacy, safety, and cost‐effectiveness of all‐trans retinoic acid/Clobetasol Propionate Compound Ointment in the treatment of mild to moderate psoriasis vulgaris: A randomized, single‐blind, multicenter clinical trial. Issue 5 (25th September 2018) - Xia, Lixin; Li, Ruoyu; Wang, Yun; Lin, Zhimiao; Zheng, Jie; Li, Xia; Lu, Qianjin; Zhang, Jing; Jin, Hongzhong; Fu, Lanqin; Zhang, Xibao; Liu, Yumei; et al.
Abstract: To assess the efficacy, safety, and cost‐effectiveness of all‐trans retinoic acid/Clobetasol Propionate Compound Ointment and calcipotriol/betamethasone dipropionate ointment in the treatment of mild‐to‐moderate patients with psoriasis vulgaris. This was a randomized, single‐blind, multicenter clinical trial. A total of 240 patients were randomized to receive twice‐daily all‐trans retinoic acid/Clobetasol Propionate Compound Ointment (treatment group) or once‐daily calcipotriol/betamethasone dipropionate ointment (control group) for 4 weeks. The efficacy, safety, and cost‐effectiveness were assessed at Weeks 2 and 4. After 4 weeks, both groups showed a significant clinical improvement compared to baseline (88.33% vs. 89.83%, respectively, p  = .7112). But PASI 75 response in the treatment group was superior to the control group (44.12% vs. 28.57%, respectively, p = .0200), at Week 4. SSRI improvement rate in the treatment group was also superior to control group (67.11% vs. 59.43%, respectively, p = .0119) at Week 4. All‐trans retinoic acid/Clobetasol Propionate Compound Ointment showed a significant clinical improvement in erythema, infiltration, and scales of skin lesions and PASI score compared to baseline. 1.67% of patients (treatment group) reported adverse reactions compared to 2.50% (control group) with no statistical significance. In addition, the cost‐effectiveness assessment showed a higher cost‐effectiveness of the treatment group compared to the control group in 4 weeks (199.25 vs. 801.51). All‐trans retinoic acid/Clobetasol Propionate Compound Ointment was effective and safe in the treatment of psoriasis vulgaris with similar efficacy as calcipotriol/betamethasone dipropionate ointment and lower treatment costs.